The Attitude of Egyptian Psychotherapists Towards Internet-Based Psychotherapy - Ahmed Abdullah (Umm Al-Qura University, 2022)
The current study aims at revealing the nature of attitude of psychotherapists towards Internet-based psychotherapy. The study used a tool to measure the attitude of the psychotherapist towards internet-based psychotherapy, prepared by re-searcher, with consideration of the psychometric properties. The sample of the study consisted of (156) psychotherapists from psychiatric hospitals and clinics in Egypt (60 males, 96 females), whose ages ranged between (26 to 53) years. The results of the study indicated that there is a positive attitude towards Internet-based psychotherapy with a relative weight of (59%), and this was in service of the therapist, then service of the case, and finally service of the therapeutic process. It was also found that there is a positive correlation between the number of hours of daily use of Internet-based psycho-therapy and total score of attitude of Internet-based psychotherapy and all its dimensions (service of case, therapist and therapeutic process). There was a negative correlation between age and both the total score of the positive attitude of Internet-based psychotherapy and all its dimensions. Internet based psychotherapists had higher scores compared to tra-ditional psychotherapists (face to face) in the positive attitude towards Internet-based psychotherapy and all its dimen-sions. Whereas, females had high degrees compared to males in the positive attitude towards Internet-based psychotherapy in the service of therapeutic process only.